2019
DOI: 10.1590/1678-4499.20180197
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of floral abnormalities in a population generated from sexual polymorphism aiming at recurrent selection in papaya

Abstract: The aim of this study was to estimate the percentage of deformed fruits (carpelloid, pentandric, and bananoid), summer sterility, repeatability coefficients, and correlations among the variables for floral abnormalities; and select genotypes with the lowest incidence of deformed fruits and summer sterility. In the experiment, which involved 254 plants, traits were evaluated using the digital-phenotypic method and the obtained images were processed and analysed using ImageJ v1.48 software with the Cell Counter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…Luz et al (2015) found lower means of 24.30, 14.98 and 0.66 for these same traits, respectively, when evaluated papaya hybrids. Moreira et al (2019), in specific studies for summer sterility and for carpeloidy and pentandry rates, verified that the repeatability coefficients varied from low to intermediate due to the quantitative nature of the evaluated traits, which are highly influenced by environmental factors. For these traits, each cycle of recurrent selection seeks to reduce deformities and sterility and increase the quantity of commercial fruits in the population.…”
Section: Genetic Variability In Ucp-c0mentioning
confidence: 64%
“…Luz et al (2015) found lower means of 24.30, 14.98 and 0.66 for these same traits, respectively, when evaluated papaya hybrids. Moreira et al (2019), in specific studies for summer sterility and for carpeloidy and pentandry rates, verified that the repeatability coefficients varied from low to intermediate due to the quantitative nature of the evaluated traits, which are highly influenced by environmental factors. For these traits, each cycle of recurrent selection seeks to reduce deformities and sterility and increase the quantity of commercial fruits in the population.…”
Section: Genetic Variability In Ucp-c0mentioning
confidence: 64%
“…High CVe values indicate low experimental precision. The low experimental precision found for NMF, NDF, and YLD may be associated with summer sterility, since sterility (NFN) increases in hotter months of the year, whereas the rates of carpellody and pentandry (NDF) increase in colder months (Moreira et al, 2019). This opposition between sterility and pentandry and/or carpellody in these months alters the data on the number of fruits, which results in high data dispersal and high experimental error.…”
Section: Estimates Of Genetic Parametersmentioning
confidence: 99%
“…Hermaphrodite flowers abort carpels and reverse to functional male flowers [ 11 ]. These floral abnormalities caused by adverse environmental conditions have a negative effect on fruit production, leading to reduced yield [ 12 , 13 ]. Uncovering the underlying mechanism of sex determination and maintenance process would result methods to improve papaya with no sex reversal to increase fruit production.…”
Section: Introductionmentioning
confidence: 99%